2015
DOI: 10.1038/srep13309
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Fibre-Based Thermoluminescence Detectors for High Resolution In-Vivo Dosimetry

Abstract: With interest in the potential of optical fibres as the basis of next-generation thermoluminescence dosimeters (TLDs), the development of suitable forms of material and their fabrication has become a fast-growing endeavour. Present study focuses on three types of Ge-doped optical fibres with different structural arrangements and/or shapes, namely conventional cylindrical fibre, capillary fibre, and flat fibre, all fabricated using the same optical fibre preform. For doses from 0.5 to 8 Gy, obtained at electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…These findings suggested that in general the Ge-doped CF demonstrated the secondorder kinetic peak [17], indicated by the shape of the glow curve which is nearly symmetric, where the high temperature half of the peak is slightly broader than the low temperature one. Based on the computerized glow curve deconvolution, the glow curve of the Ge doped CF consists of five individual glow peaks which are consistent with previous study [18]. It is observed that all peaks tend to overlap with each other throughout the studied dose range for both 6 MV ( Fig.…”
Section: Glow Curve Deconvolutionsupporting
confidence: 89%
“…These findings suggested that in general the Ge-doped CF demonstrated the secondorder kinetic peak [17], indicated by the shape of the glow curve which is nearly symmetric, where the high temperature half of the peak is slightly broader than the low temperature one. Based on the computerized glow curve deconvolution, the glow curve of the Ge doped CF consists of five individual glow peaks which are consistent with previous study [18]. It is observed that all peaks tend to overlap with each other throughout the studied dose range for both 6 MV ( Fig.…”
Section: Glow Curve Deconvolutionsupporting
confidence: 89%
“…Developments beyond the commercially available telecommunication fiber, also obtained using the MCVD technique, have included fabrication of hollow cylindrical fibers, collapsed fibers, photonic crystal fibers and flat fibers, with various Ge dopant concentrations extrinsically introduced and with various dimensions. For instance, [49] have investigated three types of Ge-doped optical fibers: conventional cylindrical fiber, capillary fiber, and flat fiber (FF), all fabricated using the same optical fiber preform, shown in Fig. 11.…”
Section: Fabricationmentioning
confidence: 99%
“…This performance is even further improved up to about 29.3 times when all the holes in the PCF are collapsed during the fiber drawing process. [49] compared the performance of a Ge-doped capillary fiber with a cylindrical fiber that was collapsed conventionally during the MCVD process and a FF that was collapsed during the fiber drawing. They have shown that the TL yield of the Ge-doped capillary is increased by a factor of 3.2 times by conventional collapsing into cylindrical form and 5.5 times by collapsing into flat shape all fabricated from the same preform.…”
Section: Structuresmentioning
confidence: 99%
“…The precision of dosimetry measurements specifies the reproducibility of the measurements under similar conditions and can be estimated from the data obtained in repeated measurements. High precision is associated with a small standard deviation of the distribution of measurement results (Podgorsak 2005 ).…”
Section: Properties Of Radiotherapy Dosimetersmentioning
confidence: 99%